Helicopter system modelling and control with matlab - Coelho, J. (2019)
This paper presents the modelling and control of a laboratory helicopter system with MatLab. In this perspective, students are motivated to investigate the dynamics, trajectory planning and control. Based on this experience, further studies on helicopter system, using more sophisticated concepts, are, then, more attractive from the students point of view.